Contingências no trabalho do assistente social em empresas: o caso de consultorias empresariais - Giampaoli, Maria Cristina (2012)
This dissertation has the objective of unveiling the dynamics of social work in business advice, providing services on an outsourced basis to companies. This condition appears with a contingency which was raised following the brazilian productive restructuring, whose impact has affected the working class as a whole, which the social worker belongs. The productive restructuring triggered, among other factors, changes in the operations of different sectors of the capitalist economic activity, changing productive structures and of the job market. The repercussions, in Brazil, among other factors, have resulted in different forms of precariousness of work and have affected the market and the conditions of work of the social worker. Comprehend those alterations in the profession, in the occupational space of the Social Work in the capitalist companies, contradictory field of activity, initially requires rescue the reasons that make the company hire a social worker; intrude the inflections caused by the profession, especially in this professional space, from the productive restructuring; and also extend the concept of consulting, as it forms and the space of services to the profession. In addition to these items, in this dissertation, the concepts about outsourcing, flexibility and precariousness are studied looking for the reflection about this dimension involved in this form of hiring. The accomplished empirical study have had the participation of six consulting professionals and it allowed observe the presence of the social work in the company apart from the contractual aspect. The professional preserves yours relative autonomy, albeit limited, in counselor activities, in the role of external consultant, within the required limits and possibilities, in the occupational space of consultancies in private companies. Without denying the conditionality placed by the employee condition, within your competencies, the professional seeks to effect the ethical-professional project